Technical development and user experience evaluation of the Computerised version of the Sydney Test of Activities of daily living in Memory disorders (C-STAM) - Ginige, Jeewani Anupama; Rana, Kritika; Belcastro, Marcus; Gunaratne, Pahan; Lillis, Sam; Numbers, Katya T.; Lin, Ping-Hsiu; Nguyen, Kathy; Tanvir, Minal; Reppermund, Simone (Frontiers in Digital Health, 2025)
The assessment of functional ability in older adults is critical for the early detection and management of age-related cognitive impairment, such as dementia and mild cognitive impairment (MCI). This paper presents a developmental and pilot user experience study of the online implementation and initial user experience evaluation of the Computerised version of the Sydney Test of Activities of daily living in Memory disorders (C-STAM), a new computerised diagnostic screening tool designed to assess functional ability in older adults with and without cognitive impairment. The technical development of the C-STAM involved translating the original STAM tasks into computerised versions, resulting in a scalable, accessible, and user-friendly tool with the potential for integration into regional and remote clinical practices. Key features of the C-STAM include automated scoring, hint options, text-to-speech functionality, a text-magnification tool, and other accessibility enhancements to accommodate diverse physical and cognitive limitations. Within the pilot study of the larger C-STAM trial, secondary feedback was sought from 30 participants (n = 13 with and n = 17 without cognitive impairment) specifically to assess the C-STAM tool's user experience (UX). This exercise did not evaluate dementia outcomes, which is planned to be reported separately. UX analysis results presented in this paper indicated a positive experience, with an average score of 5.8 ± 1.3 on a seven-point Likert scale, reflecting high perceived usability and user satisfaction. The pilot normal cognition group (n = 17) reported higher satisfaction, with an overall score of 6.4 ± 0.4. In comparison, the pilot MCI group (n = 6) and pilot dementia group (n = 7) reported lower scores of 5.1 ± 1.1 and 4.9 ± 2.1, respectively. Feedback from participants was instrumental in shaping each iteration of the tool and refining the updated version of the C-STAM that will be presented in the main validation study.